Students’ Comprehensions Ability on a Digital Storybook: a Quasi Experiment Research with Fry Readability Analysis - Hendratno, Hendratno; Istiq’faroh, Nurul; Yasin, Fajar Nur; Wibowo, Amiruddin Hadi; Ghofur, Abd. (International Journal of Language Education, 2025)
This study aims to determine the effectiveness of Fry readability-based digital storybooks on reading comprehension skills among elementary school students. The method used in this study was an experimental research design with a pretest-posttest control group design to measure students’ reading comprehension skills. The sample of this study was fourth-grade elementary school students. Data were collected through reading comprehension skills test sheets and analyzed using descriptive and statistical analysis to assess the extent to which the variables being studied align with the predetermined benchmarks. The results showed that digital storybooks based on Fry's graph readability are effective in improving the reading comprehension skills of fourth-grade elementary school students as evidenced by the n-gain test results, where the experimental class (medium) had higher scores than the control class (low). Based on the t-test, it has a significant effect with a calculated t-value greater than the table t-value. These findings show that books designed according to the grade level of students have an impact on reading comprehension skills, and the integration of digital technology in book development can attract students' attention to read with full understanding.